Improving Collaboration Skills and Thematic Learning Outcomes Theme V Sub Theme 2 Using the Student Teams Achievement Divisions (STAD) Learning Model for Class III Students at SD Negeri Bendo Samigaluh, Kulon Progo, Academic Year 2021/2022 - Yuli Winanti (Universitas Islam Indonesia, 2023)
This research aims to improve collaboration skills and student learning outcomes in thematic subjects theme V sub-theme 2 class III in SD Negeri Bendo Samigaluh for the 2021/2022 academic year through the application of the Student Teams Achievement Divisions (STAD) learning model. This type of research is Classroom Action Research (PTK) which is carried out over two cycles with each cycle consisting of 2 meetings. The subjects in this research were 5 students in class III of SD Negeri Bendo Samigaluh, Kulon Progo Regency. The data collection technique in this research is through observation. The research results show an increase in students' collaboration abilities, where in cycle I an average score of 48% was obtained and in cycle II an average score of 74.25%. Meanwhile, the data on student learning outcomes also showed an increase. This was proven in cycle I, students who met the minimum completeness criteria obtained an average score of 75% and in cycle II students who met the minimum completeness criteria obtained an average score of 100%. Therefore, the application of the Student Teams Achievement Divisions (STAD) learning model can improve collaboration skills and student learning outcomes in thematic subjects theme V, sub-theme 2, class V, SD Negeri Bendo Samigaluh for the 2021/2022 academic year.